2022
DOI: 10.3390/rs14051114
|View full text |Cite
|
Sign up to set email alerts
|

Toward Automated Machine Learning-Based Hyperspectral Image Analysis in Crop Yield and Biomass Estimation

Abstract: The incorporation of autonomous computation and artificial intelligence (AI) technologies into smart agriculture concepts is becoming an expected scientific procedure. The airborne hyperspectral system with its vast area coverage, high spectral resolution, and varied narrow-band selection is an excellent tool for crop physiological characteristics and yield prediction. However, the extensive and redundant three-dimensional (3D) cube data processing and computation have made the popularization of this tool a ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 99 publications
0
11
0
Order By: Relevance
“…The potential for high-throughput pigment phenotyping to evaluate and track growth and development, biophysical and biochemical characteristics, and diseases in crop production has been demonstrated in recent studies [ 1 , 2 , 3 , 8 , 13 ]. Spectral variations in pigment concentrations, including chlorophyll a and b , are closely correlated with differences in agronomic traits, such as plant height, grain yield, growth cycle, photosynthesis, transpiration, and water use efficiency [ 6 , 23 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The potential for high-throughput pigment phenotyping to evaluate and track growth and development, biophysical and biochemical characteristics, and diseases in crop production has been demonstrated in recent studies [ 1 , 2 , 3 , 8 , 13 ]. Spectral variations in pigment concentrations, including chlorophyll a and b , are closely correlated with differences in agronomic traits, such as plant height, grain yield, growth cycle, photosynthesis, transpiration, and water use efficiency [ 6 , 23 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Integrating hyperspectral sensors with chemometric techniques has proven effective for identifying and predicting a range of crop characteristics. For example, many studies have demonstrated the use of hyperspectral analyses to differentiate between livestock-integrated farming systems and indoor and vertical farming productions and to determine crop leaf characteristics [ 6 , 32 , 33 , 34 ]. Thus, our first and second objective proposed methods have also shown potential for increasing yield production in crops such as wheat and canola.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations